Delta G = -RT * lnK rerranging

Quadratic equations and inequalities, variation equations, function notation, systems of equations, etc.
jonny
Posts: 1
Joined: Tue Jan 07, 2014 3:30 am
Contact:

Delta G = -RT * lnK rerranging

Postby jonny » Tue Jan 07, 2014 3:41 am

Hi ,
This my first post on your forum and im sure it wont be my last :)

I have this equation...

Delta G^0 = -RT * lnK

and i need to solve for K, i have this;

delta G^0 = -RT*lnK - i get this

ln K = -(delta G^0 / RT) -- but i do not get this step- there is obviously a rule that i can think of or something can someone help me understand?

k = e ^ -(delta G^0 / RT) - i get this

Please and thank you

User avatar
little_dragon
Posts: 197
Joined: Mon Dec 08, 2008 5:18 pm
Contact:

Re: Delta G = -RT * lnK rerranging

Postby little_dragon » Tue Jan 07, 2014 12:13 pm

jonny wrote:Delta G^0 = -RT * lnK

and i need to solve for K, i have this;

delta G^0 = -RT*lnK - i get this

ln K = -(delta G^0 / RT) -- but i do not get this step- there is obviously a rule that i can think of or something can someone help me understand?

k = e ^ -(delta G^0 / RT) - i get this

its just dividing thru by -RT
:wave:


Return to “Intermediate Algebra”